Novel low-afterglow scintillator single crystal and preparation method thereof

The preparation of CsCu2Br3 single crystals by cooling and crystallization method solves the toxicity problem of existing lead-based perovskite materials and the difficulty in obtaining CsCu2I3 raw materials in copper-based halide perovskites. The prepared CsCu2Br3 single crystal has low afterglow, good environmental stability and good X-ray response performance, and is suitable for the fields of X-ray imaging and CT imaging.

CN119615365APending Publication Date: 2025-03-14SHANGHAI TECHN INST OF ELECTRONICS & INFORMATION
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410283266.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-03-13
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The existing lead-based perovskite materials have limited their better development in the optical field due to the toxicity and environmental hazards of lead. Although CsCu2I3 in copper-based halide perovskites have good application potential, their raw materials are difficult to obtain and have high prices. Few people have reported that CsCu2Br3 is a material of the same structure. The raw materials are easy to obtain and are cheap, but their chemical bonds are short and their lifespan is fast attenuated.

Method used

CsCu2Br3 single crystals were prepared by cooling and crystallization method. CsBr and CuBr were used as raw materials to prepare the precursor solution in the presence of hypophosphoric acid and hydrobromic acid. Then, sealed growth and gradient cooling were carried out, and the CsCu2Br3 single crystals were dried in a vacuum drying box at a constant temperature to prepare centimeter-level CsCu2Br3 single crystals with few nucleation points and seed crystals.

Benefits of technology

The prepared CsCu2Br3 single crystal has low afterglow characteristics and is suitable for X-ray imaging and CT imaging fields. It has good environmental stability, long service life, and good linear response to X-rays, reducing radiation damage in biological diagnosis and ensuring safety.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119615365A_ABST
    Figure CN119615365A_ABST
Patent Text Reader

Abstract

The invention discloses a novel low-afterglow scintillator single crystal and a preparation method thereof, and belongs to the technical field of materials. A novel scintillator CsCu2Br3 single crystal is prepared through a cooling crystallization method for the first time. The specific preparation method comprises the steps that CsBr and CuBr are put into a crystal growth bottle, and a hypophosphorous acid solution and a hydrobromic acid solution are sequentially added; the preparation method comprises the following steps: preparing a precursor solution, then sealing the solution, then putting the solution into an oil bath pan, setting the temperature to 90 DEG C for 24 hours, and then carrying out three-stage gradient cooling, in the first stage, rapid cooling is that the temperature of the precursor solution is reduced to 66 DEG C from 90 DEG C within 10 hours; in the second stage of extremely slow cooling, the temperature of the precursor solution is reduced to 60 DEG C from 66 DEG C at the speed of reducing 2 DEG C every day; in the third stage, the temperature of the precursor solution is reduced to 55 DEG C from 60 DEG C at the speed of reducing 2.5 DEG C every day until the growth of the crystal is finished, and then the crystal is put into a vacuum drying oven to be subjected to constant-temperature drying treatment for 24 hours to finally prepare the CsCu2Br3 centimeter-level single crystal with fewer nucleation points and better seed crystals, and the prepared CsCu2Br3 single crystal has the characteristic of low afterglow, and can be used for preparing the CsCu2Br3 centimeter-level single crystal. The method can be applied to the fields of X-ray imaging and CT imaging.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a novel low afterglow scintillator single crystal and a preparation method thereof, belonging to the technical field of materials. Background Art

[0002] In recent years, halide perovskites have been studied by more and more researchers because of their many advantages, including relatively low melting point, low-cost solution preparation, large absorption coefficient, excellent optical properties, high luminous efficiency, large defect tolerance, and large X-ray absorption coefficient. Therefore, they have achieved many results in the field of optics. Among them, lead-based perovskites are considered to be the most likely materials to replace traditional scintillators because they have X-ray absorption coefficients comparable to traditional scintillators, fast attenuation and efficient luminescence performance, and have very good scintillation performance. However, the toxicity of Pb itself and its harm to the environment violate the concept of green environmental protection, which in turn limits its better development. Therefore, replacing the lead element, retaining its excellent performance, and developing new lead-free perovskites have certain research significance for luminescent scintillators.

[0003] Copper-based halide perovskites have attracted the attention of many scholars due to their unique 3d and 4s electron orbitals and exhibit excellent optical properties, and have shown excellent application potential in many fields. 2 I 3 It has been applied to emit secondary light, which can work continuously for 580 hours in air, with a half-life of 150 hours in air. The response time of the prepared ultraviolet photodetector is only 50.4ms. 2 I 3 The minimum detection limit can reach 0.93nGys -1 , and the mobility-lifetime product is 0.01847 cm 2 V -1 , sensitivity is 424μCGy –1 cm –2 But as and CsCu 2 I 3 CsCu with the same crystal structure 2 Br 3 However, few people have reported it. 2 Br 3 Relative to CsCu 2 I 3 In terms of raw materials, it is easier to obtain and relatively cheaper than iodine-based ones. Secondly, it has a shorter chemical bond, which can achieve faster life decay. 2 I 3 Same CsCu 2 Br 3It also has a self-trapped luminescence mechanism, a large Stokes shift, and a small self-absorption. 2 Br 3 It also has certain potential as an X-ray detector.

[0004] Based on the above situation, this paper prepared CsCu by cooling crystallization method for the first time. 2 Br 3 Single crystal, with low afterglow characteristics, can be used in the field of radiation detection. Summary of the invention

[0005] The present invention provides a novel low afterglow scintillator single crystal and a preparation method thereof. The scintillator is a CsCu 2 Br 3 The specific preparation steps of centimeter-level single crystals are as follows:

[0006] (1) Preparation of precursor solution: adding hypophosphorous acid solution and hydrobromic acid solution to CsBr and CuBr in sequence to obtain a precursor solution;

[0007] (2) Crystal growth: The container containing the precursor solution is sealed, then kept warm, and then subjected to three-stage gradient cooling, wherein the first stage is rapid cooling, and the second and third stages are extremely slow cooling, at which point the crystal growth ends;

[0008] (3) The crystal grown in step (2) is placed in a vacuum drying oven for constant temperature drying, and finally a CsCu crystal with few nucleation points and good seed crystals is prepared. 2 Br 3 Centimeter-scale single crystals.

[0009] Preferably, in step (1), the amount of CsBr used is 0.5146 g, the amount of CuBr used is 0.7146 g, the amount of hypophosphorous acid solution used is 120 μL, and the amount of hydrobromic acid solution used is 12 mL.

[0010] Preferably, in step (2), the precursor solution is placed in an oil bath containing silicone oil to carry out a crystal growth reaction.

[0011] Preferably, the insulation temperature in step (2) is 90° C. and the insulation time is 24 h.

[0012] Preferably, the first stage in step (2) is rapid cooling: the temperature of the precursor solution is reduced from 90° C. to 66° C. within ten hours.

[0013] Preferably, the second stage of extremely slow cooling in step (2) is to reduce the temperature of the precursor solution from 66°C to 60°C at a rate of 2°C per day.

[0014] Preferably, in step (2), the third stage is extremely slow cooling: the temperature of the precursor solution is reduced from 60° C. to 55° C. at a rate of 2.5° C. per day.

[0015] Preferably, the constant temperature drying time in step (3) is 24 hours.

[0016] The scintillator prepared by the present invention is used in the fields of X-ray imaging and CT imaging.

[0017] Beneficial Effects of the Invention

[0018] (1) This invention prepares a new scintillator CsCu by cooling crystallization method for the first time 2 Br 3 Single crystal, and solved the problem of luminescence of impurities on the crystal surface.

[0019] (2) The scintillator CsCu prepared by the present invention 2 Br 3 Single crystals can be used in X-ray imaging and CT imaging because of their low afterglow.

[0020] (3) The scintillator CsCu prepared by the present invention 2 Br 3 Single crystal has good environmental stability and long service life.

[0021] (4) The scintillator CsCu prepared by the present invention 2 Br 3 Single crystals have good linear response to X-rays, which reduces radiation damage during biological diagnosis and ensures safety.

[0022] (5) The present invention opens up a new approach for the preparation of scintillators. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 The CsCu prepared in Example 1 2 Br 3 Front view of the crystal structure of a single crystal.

[0024] Figure 2 The CsCu prepared in Example 1 2 Br 3 Single crystal and powder CsCu 2 Br 3 XRD diffraction pattern of single crystal.

[0025] Figure 3 The CsCu prepared in Example 1 2 Br 3 Rocking curve test of single crystal.

[0026] Figure 4The CsCu prepared in Example 1 2 Br 3 SEM scan and EDS surface scan of single crystal.

[0027] Figure 5 The CsCu prepared in Example 1 2 Br 3 TGA curve of single crystal powder.

[0028] Figure 6 The CsCu prepared in Example 1 2 Br 3 DTA curve of single crystal powder.

[0029] Figure 7 The CsCu prepared in Example 1 2 Br 3 The luminescence spectrum and absorption spectrum of the single crystal. From left to right are CsCu 2 Br 3 Optical photograph of a single crystal, optical microscope photograph (100 times), and luminescence under a 254nm ultraviolet lamp in liquid nitrogen.

[0030] Figure 8 The CsCu prepared in Example 1 2 Br 3 UV-visible-near-infrared absorption spectra of single crystals.

[0031] Fig. 9 The CsCu prepared in Example 1 2 Br 3 Photoluminescence spectrum of the single crystal under 266nm excitation.

[0032] Fig.10 The CsCu prepared in Example 1 2 Br 3 X-ray absorption coefficient diagram of single crystal, CsI, and Lu:AG in the energy range of 0.001MeV to 100MeV. The inset shows the absorption coefficient in the biological test range.

[0033] Fig.11 The CsCu prepared in Example 1 2 Br 3 Single crystal and X-ray excitation spectra of Lu:AG.

[0034] Fig.12 The CsCu prepared in Example 1 at different times 2 Br 3 The luminescence intensity of a single crystal excited by X-rays.

[0035] Fig.13The CsCu prepared in Example 1 2 Br 3 Comparison of afterglow intensity between single crystal and CsI.

[0036] Fig.14 The CsCu prepared in Example 1 2 Br 3 Linear fitting plot of detection limit test for single crystal. DETAILED DESCRIPTION

[0037] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and through specific implementation methods. However, the following embodiments are only simple examples of the present invention and do not represent or limit the scope of protection of the present invention. The scope of protection of the present invention shall be subject to the claims.

[0038] Example 1

[0039] A novel low afterglow scintillator single crystal preparation method specifically includes the following steps:

[0040] (1) Preparation of precursor solution: 0.5146 g of CsBr and 0.7146 g of CuBr were placed in a crystal growth bottle, 120 μL of hypophosphorous acid solution was first added to prevent CuBr from being oxidized, and then 12 mL of hydrobromic acid solution was added to obtain a precursor solution.

[0041] (2) Crystal growth: Seal the crystal growth bottle. First, apply a layer of sealing silicone grease on the threaded mouth of the growth bottle. After tightening the bottle cap, use sealing tape to seal it again. Put the sealed crystal growth bottle into a silicone oil bath and keep it at 90°C for 24 hours. Then, reduce the temperature from 90°C to 66°C within ten hours, then reduce the temperature from 66°C to 60°C at a rate of 2°C per day, and finally reduce the temperature from 60°C to 55°C at a rate of 2.5°C per day. At this point, the crystal growth is completed.

[0042] (3) The crystal grown in step (2) was placed in a vacuum drying oven for 24 hours of constant temperature drying treatment, and finally a rod-shaped CsCu with a size of 9 mm*3 mm*3 mm and fewer nucleation points was obtained. 2 Br 3 Single crystal.

[0043] The CsCu prepared in this example 2 Br 3 The crystal structure of a single crystal is shown in the figure Figure 1 As shown in the figure, it can be seen that each Cu + Atom and four Br - connect to form a tetrahedron structure, which then connects to form an octahedron, which extends along the z-axis to form Cu 2 Br 6Octahedral chain, each row edge shares Cu 2 Br 6 Octahedral chain, surrounded by six Cs + Ions surround and isolate to form a unique core-shell structure. 2 Br 3 A one-dimensional rod-shaped single crystal was formed along the Z-axis direction.

[0044] In order to determine the CsCu 2 Br 3 The phase and crystal quality of single crystals were tested by X-ray diffractometer. 2 Br 3 Single crystal and CsCu ground from single crystal 2 Br 3 The XRD diffraction pattern of the single crystal powder was also tested for the rocking curve. Figure 2 As shown in the figure, it can be seen that CsCu 2 Br 3 The single crystal powder XRD can match PDF#77-1568 very well, proving that CsCu 2 Br 3 The single crystal was successfully prepared. The single crystal XRD tested the {001} crystal plane family, and the spectrum showed (100), (200), (300), (400) crystal planes. The spectrum did not show other crystal planes and impurity peaks, proving that CsCu 2 Br 3 The single crystal surface is free of impurities and has high mirror integrity. The rocking curve of the (100) crystal plane is as follows Figure 3 As shown in the figure, it can be seen that the half-peak width is 0.042°, indicating that the prepared CsCu 2 Br 3 Single crystal has high crystallinity and high quality.

[0045] In order to determine the CsCu 2 Br 3 The morphology and uniformity of element distribution on the single crystal surface are 2 Br 3 The single crystal surface was tested by SEM and EDS, and the results are as follows Figure 4 As shown in the figure, it can be seen that CsCu 2 Br 3 The surface of the single crystal is relatively flat and has sharp edges and corners. The three elements are evenly distributed. The content of Br is much higher than that of the other two elements. The distribution contents of Cs, Cu and Br are 18.61%, 35.98% and 45.40% respectively. The percentage of elements is roughly 1:2:3, which is consistent with CsCu 2 Br 3The element distribution ratio of the single crystal shows that the CsCu with relatively good quality is obtained. 2 Br 3 Single crystal.

[0046] Thermal stability is CsCu 2 Br 3 The good thermal stability is an important property of single crystal, which can effectively ensure that the material can operate stably and continuously without thermal decomposition. Therefore, the CsCu prepared in this example was tested. 2 Br 3 The thermal stability of the single crystal is shown in Figure 2. Figure 5 As shown, from Figure 5 It can be seen from room temperature to 500℃, CsCu 2 Br 3 The single crystal powder did not lose weight before 477 degrees Celsius, and lost only 0.23% of its weight at 500 degrees Celsius. Figure 6 It can be seen that CsCu 2 Br 3 The melting point of the single crystal powder is 354°C, indicating that the prepared CsCu 2 Br 3 Single crystal has good thermal stability.

[0047] The CsCu obtained in this example 2 Br 3 The optical properties of single crystals are tested. Figure 7 A photo of a single crystal with high transparency and large size is shown; when observed under a 100x optical microscope, the surface of the crystal is uniform, free of pits and impurities; under the irradiation of an ultraviolet lamp in liquid nitrogen, the crystal emits a bright and pure yellow light. Figure 8 CsCu 2 Br 3 The ultraviolet absorption spectrum of the single crystal shows that the highest absorption peak is at 285nm (4.35eV), and the second highest peak is at 323nm (3.84eV). The entire absorption band is basically in the ultraviolet band (1nm-400nm), and there is almost no absorption in the visible light band (400nm-780nm), which can effectively reduce the reabsorption of crystal luminescence. The illustration is based on the absorption spectrum fitting, showing that CsCu 2 Br 3 The optical band gap value of the single crystal is 3.65eV, which has a relatively high band gap value.

[0048] Fig. 9 The CsCu prepared in this example 2 Br 3The photoluminescence spectrum of the single crystal in the excitation light band of 266nm. It can be seen from the figure that the luminescence center of the photoluminescence spectrum is located at 580nm (2.14eV), and 580nm belongs to the yellow luminescence band, which is consistent with the result of the optical luminescence picture taken of yellow light emission. At the same time, the photoluminescence spectrum shows that its half-peak width is 68nm, and the Stokes shift reaches 295nm, which is a broadband emission. Usually, the band edge emission has a narrow half-peak width and a small Stokes shift. At the same time, a large photoluminescence half-peak width and a large Stokes shift can be considered to be a self-trapped exciton luminescence mechanism or a defect luminescence mechanism. However, during the experiment, it can be seen from the ultraviolet absorption spectrum that in addition to the absorption at the band edge, no absorption peaks that may exist for defect emission can be found. At the same time, defect luminescence will cause the luminescence of the material itself to become uneven due to the unevenness of vacancies. In CsCu 2 Br 3 The luminescence photo of the single crystal under ultraviolet excitation shows that the crystal itself emits bright and uniform yellow light, thus eliminating the possibility of defect luminescence. 2 Br 3 The luminescence mechanism of single crystals may originate from self-trapped exciton luminescence, just like other low-dimensional copper-based halides.

[0049] The X-ray absorption capacity has a great influence on the performance of the scintillator, because the larger the absorption coefficient, the stronger the X-ray blocking ability, and the more effective the X-ray absorption. The X-ray photon cross section database was used to obtain the X-ray absorption coefficients of CsI, Lu:AG, and CsCu prepared in this example. 2 Br 3 The X-ray absorption coefficients of the three materials in a single crystal are as follows: Fig.10 As shown, CsCu 2 Br 3 Comparison of the absorption coefficients of single crystals and commercial scintillators (CsI, Lu:AG) shows that before 0.01 MeV, CsCu 2 Br 3 Single crystals have absorption coefficients comparable to commercial scintillators, ranging from 0.01MeV to 0.1MeV CsCu 2 Br 3 The single crystal always maintains an excellent absorption coefficient, which is slightly inferior at 0.1MeV to 1MeV. After 1MeV, the absorption coefficients of the three scintillators tend to be consistent. In the field of medical X-ray imaging (18KeV-30KeV), which is also the field where scintillators are most widely used, it is found that CsCu 2 Br 3 The single crystal absorption coefficient is much better than that of traditional scintillator CSI and comparable to that of Lu:AG. The higher absorption coefficient means that a thinner thickness can be used to fully absorb X-rays. 2 Br3 Single crystals have the potential to be used as scintillators.

[0050] In order to characterize CsCu 2 Br 3 The scintillation properties of single crystals were first tested by X-ray excitation spectra on a fluorescence spectrometer with an X-ray tube. Fig.11 CsCu 2 Br 3 The luminescence spectrum of the single crystal is consistent with that of ultraviolet excitation light, and the emission center is from 580nm. This shows that the relaxation of the excited state before luminescence is consistent with that under ultraviolet excitation, and both are caused by electrons recombining with holes from the same self-trapped state and then emitting light.

[0051] At the same time, in order to understand CsCu 2 Br 3 The efficiency of a single crystal in converting X-rays into visible light at 580 nm is calculated. 2 Br 3 The relative light yield of the single crystal is 5800photon·MeV -1 , indicating that it has potential for application in the field of scintillation.

[0052] The environmental stability of the scintillator is also an extremely important performance. High environmental stability can ensure the long-term use of the scintillator and reduce the difficulty of packaging. Fig.12 As shown, the intensity comparison diagram of the X-ray excitation spectrum of the sample of this embodiment is shown 24 hours and 2520 hours after preparation. The sample is kept in an air environment. After 2520 hours, CsCu 2 Br 3 The luminous intensity of the single crystal has been significantly reduced. Comparison of the integrated intensity of the two X-ray excitation spectra shows that after 2520 hours, the integrated intensity dropped to 40%. Such environmental stability is far superior to other perovskites, ensuring that the scintillator can have a longer service life.

[0053] Afterglow level is another core parameter of scintillator. Long afterglow will greatly affect the imaging quality of X-rays, reduce the overall resolution, cause artifacts, etc. In the field of fast imaging CT, afterglow is required to be reduced to less than one thousandth within 10ms. Fig.13 As shown, the commercial scintillator CsI and the CsCu prepared in this example were tested. 2 Br 3 The afterglow level of the single crystal, after the X-ray cutoff, the afterglow level of the commercial scintillator CsI is: 3ms down to 1.1%, 10ms down to 0.34%, 30ms down to 0.09%, CsCu 2 Br3 The afterglow level of the single crystal is: 3ms down to 0.07%. From the test results, CsCu 2 Br 3 The single crystal can drop to less than one thousandth of the initial intensity within 3ms, and has the potential to be used in the field of CT imaging. The afterglow of the mainstream commercial scintillator CsI can only reach 0.34% within 10ms, and even after 30ms, the afterglow will drop to less than one thousandth. In comparison, CsCu 2 Br 3 The afterglow level of single crystal is quite excellent and is quite suitable for use as a scintillator.

[0054] The CsCu prepared in this example 2 Br 3 The single crystals were tested for X-ray detection limits, such as Fig.14 As shown, the test results show that CsCu 2 Br 3 The single crystal has a good linear response to X-rays at 5 μGy air / s to 20μGy air / s, after extending the fitting curve, the X-ray dose when the signal-to-noise ratio is 3 is 0.569μGy air / s, higher than the 5.5μGy required for biological diagnosis air / s X-ray dose is a whole order of magnitude smaller, which can reduce radiation damage during biological diagnosis and ensure safety.

Claims

1. A new type of low afterglow scintillator single crystal, characterized by: The scintillator is a centimeter-scale single crystal with a structure of CsCu2Br3.

2. The method for preparing the novel low afterglow scintillator single crystal according to claim 1, characterized in that: The specific preparation steps are as follows: (1) Preparation of precursor solution: adding hypophosphorous acid solution and hydrobromic acid solution to CsBr and CuBr in sequence to obtain a precursor solution; (2) Crystal growth: The container containing the precursor solution is sealed, then kept warm, and then subjected to three-stage gradient cooling, wherein the first stage is rapid cooling, and the second and third stages are extremely slow cooling, at which point the crystal growth ends; (3) placing the crystal grown in step (2) into a vacuum drying oven for constant temperature drying, and finally preparing a CsCu2Br3 centimeter-level single crystal with few nucleation points and good seed crystals.

3. The method for preparing the novel low afterglow scintillator single crystal according to claim 2, characterized in that: In step (1), the amount of CsBr used is 0.5146 g, the amount of CuB used is 0.7146 g, the amount of hypophosphorous acid solution used is 120 μL, and the amount of hydrobromic acid solution used is 12 mL.

4. The method for preparing the novel low afterglow scintillator single crystal according to claim 2, characterized in that: In step (2), the precursor solution is placed in an oil bath filled with silicone oil to carry out a crystal growth reaction.

5. The method for preparing the novel low afterglow scintillator single crystal according to claim 2, characterized in that: In step (2), the insulation temperature is 90° C. and the insulation time is 24 h.

6. The method for preparing the novel low afterglow scintillator single crystal according to claim 2, characterized in that: The first stage in step (2) is rapid cooling: the temperature of the precursor solution is reduced from 90° C. to 66° C. within ten hours.

7. The method for preparing the novel low afterglow scintillator single crystal according to claim 2, characterized in that: The second stage of extremely slow cooling in step (2) is to reduce the temperature of the precursor solution from 66°C to 60°C at a rate of 2°C per day.

8. The method for preparing the novel low afterglow scintillator single crystal according to claim 2, characterized in that: The third stage of step (2) is extremely slow cooling: the temperature of the precursor solution is reduced from 60°C to 55°C at a rate of 2.5°C per day.

9. The method for preparing the novel low afterglow scintillator single crystal according to claim 2, characterized in that: The constant temperature drying time in step (3) is 24 hours.

10. Application of the scintillator single crystal according to claim 1 in the fields of X-ray imaging and CT imaging.